Therapeutic potential of epigallocatechin gallate in gynecologic cancer, endometriosis, polycystic ovary syndrome: a mechanistic and translational perspective - Sanlier, Nazlı Tunca; Turkoglu, İnci; Sacinti, Koray Gorkem; Sanlier, Nevin (Frontiers in Nutrition, 2026)
Tea, among the most widely consumed beverages worldwide, is rich in polyphenolic compounds known as catechins, particularly epigallocatechin gallate (EGCG). This review aims to synthesize recent findings and ongoing controversies concerning the role of tea-derived catechins in gynecologic diseases while also outlining key priorities for future research to address existing knowledge gaps. A comprehensive literature search was conducted across the following electronic databases: PubMed, Medline, Embase, Cochrane Library, CINAHL, Web of Science, Scopus, Google Scholar, and ScienceDirect. Epigallocatechin gallate molecules exhibit diverse biological activities, including antioxidant, anti-inflammatory, antiproliferative, and epigenetic effects, primarily through the modulation of key cellular pathways such as PI3K/Akt, MAPK, and NF-κB. Growing evidence from in vitro, in vivo, and limited clinical studies suggests that catechins may be of therapeutic value in the treatment of gynecological conditions, including endometrial, ovarian, cervical, and vulvar cancers, as well as non-neoplastic disorders such as polycystic ovary syndrome and endometriosis. EGCG, as both an antioxidant and a pro-oxidant, has been shown to sensitize cancer cells to chemotherapy, regulate hormonal imbalances, and suppress inflammatory responses. However, discrepancies in findings between studies, largely due to heterogeneity in dosage, bioavailability, and study design, limit definitive conclusions. While promising, these compounds require validation through robust, large-scale, and standardized clinical trials to define optimal dosing strategies, assess long-term safety, and determine their roles in routine gynecological practice.